(untitled) (Journal of Science and Technology, 2016)
The main purpose of the study was to examine the level of household expenditure on dairy products and to identify the principal factors that influence the level of consumption expenditure on dairy products across households in Accra and Kumasi. Structured questionnaire was used to elicit primary information from a total of 303 households through a multi-stage sampling approach. The double logarithmic multiple regression model was found to be the most suitable functional form and was thus used to examine the major determinants of household dairy consumption expenditure patterns. The principal determinants of aggregate dairy consumption expenditure were identified as income level of household head, distance from home to purchase point and the level of urbanization of consumer’s home location. The study revealed that the elasticity of expenditure on dairy products (i.e. evaporated milk and raw fresh milk) with respect to own price is unity. Elasticity of expenditure with respect to income level and prices of substitutes was found to be less than unity. It became evident from the study that raw fresh milk is an inferior commodity in Ghana. However, evaporated milk was found to be a normal commodity.